Spectrophotometric Determination of p-Nitrophenol under ENP Interference - Hui Xia; Wenjing Zhang; Zhijie Yang; Zhenxue Dai; Yuesuo Yang (Journal of Analytical Methods in Chemistry)
Engineered nanoparticles (ENPs) have been widely developed in various fields in recent years, resulting in an increasing occurrence of nanoparticles in the natural environment. However, the tiny substances have created unexpected confusion in environmental sample testing due to the negative nanoeffect of ENPs. In this paper, a novel technique of spectrophotometric determination of p-nitrophenol (PNP) was developed under the interfering impact of nano-Fe(OH)3, widely distributed in the natural environment as a typical example of ENPs. Because of the strong absorption at the two characteristic peaks of PNP, namely, 317 nm and 400 nm, nano-Fe(OH)3 interfered with the colorimetric determination of PNP. Thus, the developed testing method, with HCl acidification at 60°C and ascorbic acid (AA) masking FeCl3, was proposed and successfully realized the accurate determination of PNP in water samples by ultraviolet spectrophotometry with 317 nm as the absorption wavelength. The final colorimetric system of 5% HCl, 10% CH3OH, and 1% ascorbic acid was confirmed by optimized batch experiments, and the optimum condition of acidification pretreatment was heating at 60°C for 20 min. Further results demonstrated that the proposed novel method had good accuracy and reproducibility even in high-salinity natural water bodies such as groundwater and surface water. The testing technique presented in this paper provided an interesting and useful tool for problem solving of PNP surveys under ENPs’ interference and practically supported water quality assessment for a better environment.